Multiculturalidad, movilizaciones y representaciones sociales: La destrucción de la estatua de Pedro de Valdivia, Chile: Multiculturalism, Mobilizations and Social Representations: The Destruction of the Statue of Pedro de Valdivia, Chile - Parada Ulloa, Marcos; Dörner Paris, Anita; Nass Álvarez, Juan Luis (Revista de Filosofía, 2021)
This work is a case study of the statue of Pedro de Valdivia located in the city of Temuco with the purpose of understanding its meaning, the dispute over interpretation and what this image represents from the perspective of multiculturalism and social representations. This has an emotional and symbolic meaning, being projected in the public space. The dispute over interpretation refers to the fact that a social group questions the statue of Pedro de Valdivia, whose meanings are questioned both individually and collectively, favoring the cultural integration of society with a resignification of the object. Objectification and anchoring allow transforming the abstract and strange into concrete and familiar, as well as incorporating meanings and new symbolisms on the statue.